An investigation into the design of precision weeding mechanisms for inter or intra-row weed control - Dedousis, Athanasios (Cranfield University, 2007)
There is an increasing interest in the use of mechanical intra-row weeders because of concern over environmental degradation and a growing demand for organically produced food. The aim of this study was to investigate the factors that influence the design of precision weeding mechanisms for inter-and intra-row weed control. The purpose is to increase the understanding of the dynamics of the soil-machine interactions and to develop a system for either organic farming or to reduce the environmental loading of agrochemicals in conventional agriculture. Both the graphical computer simulation studies and the use of a mathematical model (O’Dogherty et al., 2007) for the kinematics of discs were used as tools to aid the disc design to determine the optimum geometric characteristics for a rotating disc that will be able to treat the intra-row area between the crop plants undisturbed circle. The model has wide applicability for the interactive design of discs for a range of crops. A force prediction model for shallow asymmetric static and rotating discs (about a vertical axis) developed to predict the forces on rotating discs. The model takes into account the geometric parameters of the discs, the speed of operation, the working depth and the physical properties of the soil based upon those required for the general soil mechanics equation which obeys the Mohr-Coulomb failure criterion. A comparison of all experimental work encompassing the laboratory experiments with non-rotating and rotating discs, incorporating the deflection effect of the shaft when working at 0o inclination angle showed that the model is able to predict the draught force with good accuracy. The predicted forces were 3.5% more than the measured forces overall for a linear regression line (with a coefficient of determination of 0.7) and 61% of the data were within bounds of ± 25% a line of equal magnitude. The effect of working depth, inclination angle and disc geometry on draught and penetration force requirements for flat and convex discs were assessed under controlled laboratory conditions. Because of its simplicity a flat disc was an obvious one to study as it is a circular blade with incorporating a cut-out sector, whilst the convex disc has the advantage of underside clearance. The effect of the concavity on soil failure proved to be of interest by providing smaller aggregates. Four inclination angles (0o - 15o) were examined at 0.5 m s-1 (1.8 km h-1) driving speed and 1 rev s-1 rotational speed at 10 mm deep. Four depths (10 mm - 25 mm) were examined at 0.5 m s-1 driving speed and 1 rev s-1 rotational speed at 10 mm deep and 0o inclination angle were tested under controlled conditions. Inclination angle and disc geometry had a significant effect on disc forces and soil failure. A small increase in inclination angle to the direction of travel reduces the magnitude of draught and vertical force by 70% and 80% respectively on average for both flat and convex disc geometries. The convex disc requires 15% less draught force than an equivalent flat disc. This allowed the optimum working parameters for a disc to be selected to eliminate the weeds with the minimum force requirements. The results of a field experiment after 16; 23; and 33 days transplanting with a working speed of 0.5 m s-1 (1.8 km h-1) showed that the proposed novel mechanical weed control system can achieve a weed reduction within the crop row up to 87%. The disc-hoe has a lower cost for an area of 125 ha of £81 ha-1,in comparison to £139 ha-1 for the inter-row and hand weeding combination and £690 ha-1 for a six man gang manual intra-row weeding, for two passes. It is also less expensive than the cost of the 24 m tractor mounted sprayer of £100 ha-1 The use of the rotating disc-hoe for mechanical weed control would have the benefits of lower mechanical weeding cost, increased potential for organic production and reduction in the number of weeding operations through better targeting to minimise problems caused by frequent soil disturbance and reduced herbicide use having the benefits of environmental advantage.